The effect of patient participation on trust in primary health care physicians among patients with chronic diseases: the mediating role of perceived value - Zhang, Li; Wang, Baokai; Fu, Chang (Frontiers in Public Health, 2025)
BackgroundLow levels of trust in primary health care physicians (PHCPs) significantly decrease primary health care utilization among patients with chronic diseases. In the context of the Chinese government having made considerable efforts to strengthen the development of chronic disease management within Chinese primary health care institutions, it is of great theoretical and practical significance to investigate ways to improve the trust in PHCPs among patients with chronic diseases. This study aimed to explore the impact of patient participation on patient trust in PHCPs, and to examine the mediating role of patient perceived value on this relationship.MethodsThis study included 884 patients with chronic diseases from a cross-sectional survey conducted in Shandong Province, China, from July to August 2023, using a multistage stratified sampling method. Structural equation modeling was conducted to investigate the relationships between patient participation, patient perceived value, and patient trust.ResultsPatient participation had a direct effect on patient trust (Bias-corrected 95%CI = 0.10–0.20; Percentile 95%CI = 0.10–0.20). Furthermore, patient perceived value mediated the relationship between patient participation and patient trust (Bias-corrected 95%CI = 0.15–0.32; Percentile 95%CI = 0.15–0.32).ConclusionPatient participation cannot only directly and positively predict patient trust in PHCPs, but also indirectly affect patient trust through patient perceived value. These findings highlight the importance of patient participation and perceived value to improve the trust in PHCPs among patients with chronic diseases. Therefore, health managers and policymakers should facilitate patient participation and recognize patient perceived value during the service delivery process.